Turn That Racket Down! Physical Anhedonia and Diminished Pleasure From Music. (July 2015) - Nusbaum, Emily C.; Silvia, Paul J.; Beaty, Roger E.; Burgin, Chris J.; Kwapil, Thomas R.
Why do some people not enjoy listening to music as much as others? Two studies explored whether people high in physical anhedonia—an aspect of schizotypy that is associated with reduced pleasure from physical stimuli—are less engaged in the musical world than other people. Study 1 examined individual differences in music engagement and experience. People with higher levels of physical anhedonia reported valuing music less, experiencing fewer aesthetic emotions in response to music, liking fewer genres of music, and having less music experience. Study 2 used experience sampling to examine how individual differences in physical anhedonia predicted music engagement, music listening habits, and the aesthetic experiences of music in everyday life. During a typical week, people with higher levels of physical anhedonia spent less time listening to music. Taken together, these results suggest that as physical anhedonia increases, people become increasingly detached from and disinterested in music.